The origin of the luminous blue variable Wray 15-0751 - Comerón, Fernando; Pasquali, Anna; Brillerty, Laura; Armas, J. P. (Astronomy and astrophysics, 2025)
Context. Luminous blue variables (LBVs) are an elusive stage of the post-main sequence evolution of massive stars. Wray 15−0751 is one of the few LBVs known to belong to a cluster, FSR 1570, to which we can constrain the distance and kinematics thanks to Gaia, providing additional valuable information of the star. Aims. We jointly consider the Gaia astrometric information on Wray 15−0751 and its cluster, plus its spectral classification and that of the brightest cluster members, to assess the evolutionary path leading to the current stage of the star and infer some properties of the likely binary system that originated it. Methods. In addition to the astrometry from Gaia DR3 we present classification spectroscopy in the visible of Wray 15−0751 and the 18 brightest cluster members of FSR 1570, plus new photometric and spectroscopic observations of Wray 15−0751, which we analyzed jointly with published evolutionary tracks. Results. Astrometry confirms the membership of Wray 15−0751 in its host cluster, without displaying any evidence of a kick velocity. The current cluster turnoff at late O types implies an age of 10.2+6.3−3.2 Myr. Together with the results of existing far-infrared observations pointing to it having recently undergone the red supergiant phase, we conclude that Wray 15−0751 is most likely a blue straggler now in the blue loop, resulting from a complete merger of two members of a close binary system with similar initial masses, not much in excess of ∼20 solar masses each.
Online verfügbar: 05. November 2025
Gesehen am 17.02.2026